Lower Arch Crowding In Relation To Periodontal Disease (Mustansiria Dental Journal, 2018)
A clinical examination was done to study the relationship between crowding and periodontal health status in lower anterior region. The occurrence of crowding was recorded in fifty adult males with class I angle occlusal relationship who have not been received orthodontic treatment before. The sample was divided into two groups: a crowded group of 25 males presented with crowding in the lower anterior teeth, and a normal group of 25 males presented with normal occlusal features and with no crowding.Scaling (supra and sub gingival debridement) and polishing were done for all the subjects, plaque and gingival indices were scored before treatment, and then re-scored at one, two, three and four weeks after treatment.It was found that the gingival index and plaque index are reduced in their value in the normal group, while the gingival and plaque indices tend to return to their original pretreatment values in the group of crowded lower anterior teeth and much faster than that of a normal group.